Teknik Observasi Lingkungan Berbasis Kearifan Lokal dalam Meningkatkan Kemampuan Berpikir Kritis - Uli, Indriyana; Lizawati, Lizawati (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2019)
This research is the application of local kearipan-based environmental observation techniques in improving the critical thinking skills of IKIP PGRI Pontianak students. Based on the objectives of the research, the method to be implemented is using a learning strategy with local kearipan based environmental observation techniques with a qualitative descriptive method in the form of Classroom Action Research. The results showed that the study of old literature with observation techniques based on local wisdom can improve critical thinking of class B students in the morning of semester IV at IKIP PGRI Pontianak. This is indicated by the initial condition of only 68.75% of students who get completeness, then it increases in cycle I to 75% and increases again in cycle II to 90%. Based on the increase in the average value and the percentage of students completeness shows that environmental observation techniques based on local wisdom can improve the critical thinking of IKIP PGRI Pontianak students.Keywords: Application; Observation; Environment; Thinking; Critical.